2020
DOI: 10.1002/jcla.23509
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA NEAT 1 and its target microRNA‐125a in sepsis: Correlation with acute respiratory distress syndrome risk, biochemical indexes, disease severity, and 28‐day mortality

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Geng et al (Geng et al, 2019) demonstrated that lncRNA MALAT1 expression was elevated in adults with sepsis and suggested lncRNA MALAT1 could be developed as a potential biomarker for facilitating diagnosis and management in sepsis. Likewise, high lncRNA NEAT1 expression showed close correlation with increased disease risk, enhanced severity, and higher 28-day mortality in sepsis (Yang et al, 2020). Bai et al (Bai et al, 2020) also identified four pediatric sepsisassociated lncRNAs, including RP11-1220 K2.2.1-7, ANXA3-2, TRAPPC5-1, and ZNF638-1.…”
Section: Introductionmentioning
confidence: 84%
“…Geng et al (Geng et al, 2019) demonstrated that lncRNA MALAT1 expression was elevated in adults with sepsis and suggested lncRNA MALAT1 could be developed as a potential biomarker for facilitating diagnosis and management in sepsis. Likewise, high lncRNA NEAT1 expression showed close correlation with increased disease risk, enhanced severity, and higher 28-day mortality in sepsis (Yang et al, 2020). Bai et al (Bai et al, 2020) also identified four pediatric sepsisassociated lncRNAs, including RP11-1220 K2.2.1-7, ANXA3-2, TRAPPC5-1, and ZNF638-1.…”
Section: Introductionmentioning
confidence: 84%
“…Apart from exploring the dysregulation of lnc‐NEAT1 and miR‐125a, various studies also note that they are inter‐correlated in sepsis, coronary artery disease, etc. 16 , 29 In line with previous studies, our study also revealed a negative correlation was found between circulating lnc‐NEAT1 and miR‐125a in the pediatric AR patients, but not in DCs or HCs, which could be explained by that in healthy subjects or non‐hyperimmune diseases, lnc‐NEAT1 and miR‐125a expressions were in the state of immune homeostasis and neither of them was dysregulated, while the occurrence of AR might cause excessive imbalance between lnc‐NEAT1 and miR‐125a and further resulted in the enhanced negative correlation between them. 30 Thus, the lnc‐NEAT1 expression was negatively correlated with the miR‐125a expression in the pediatric AR patients, while no correlation was observed between the lnc‐NEAT1 and miR‐125a expressions in DCs or HCs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NEAT1 was reported to enhance the immune response through activation of the highmobility group box 1 (HMGB1)/receptors for advanced glycation end products (RAGE) and NF-kB pathway, which exacerbated lung epithelial cell injury in sepsis mice (52). Subsequent studies in sepsis patients further demonstrated that the direct interaction of NEAT1 with the target miR-125a increased apoptosis of lung epithelial cells, which ultimately led to poor prognosis of ARDS (43). Chen et al found that overexpression of NEAT1 could inhibit miR-204 and activate the NF-kB pathway, aggravating sepsis-induced mesangial cell injury (53).…”
Section: The Roles Of Lncrnas In Sepsismentioning
confidence: 99%
“…Negatively regulated by MALAT1, hsa-miR-346 played a vital role in the progression of sepsis by inhibiting the expression of SMAD3 ( 41 ). Working as the sponge of miR-125, NEAT1 might upregulate MCEMP1 to promote inflammatory factor activities as well as apoptosis, which might serve as a novel biomarker for treatment of septic patients ( 42 , 43 ). Another in vitro study demonstrated that NEAT1 was observed to regulate miR-495-3p/signal transducers and activators of transcription axis and miR-211/phosphoinositide-3-kinase/protein kinase B axis in inflammatory process of sepsis ( 44 ).…”
Section: The Roles Of Lncrnas In Sepsismentioning
confidence: 99%